2015
DOI: 10.1016/j.ijhydene.2015.02.124
|View full text |Cite
|
Sign up to set email alerts
|

Progress in thermochemical hydrogen production with the copper–chlorine cycle

Abstract: This paper presents recent advances by an international team of five countries -Canada, U.S., China, Slovenia and Romania -on the development and scale-up of the copper chlorine (Cu-Cl) cycle for thermochemical hydrogen production using nuclear or solar energy. Electrochemical cell analysis and membrane characterization for the CuCl/HCl electrolysis process are presented. Constituent solubility in the ternary CuCl/HCl/H2O system and XRD measurements are reported in regards to the CuCl2 crystallization process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 61 publications
(40 reference statements)
0
27
0
Order By: Relevance
“…Canadian national laboratories (CNLs) and the University of Ontario (UOIT) have extensively investigated each step and finally demonstrated individual steps of Cu–Cl cycle . Performance of 300‐cm 2 electrolytic cell was evaluated resulting in a stable current density of 0.55 A/cm 2 at 0.7 V, and 98% of the theoretical hydrogen production rate for over 1600 hours was reported .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canadian national laboratories (CNLs) and the University of Ontario (UOIT) have extensively investigated each step and finally demonstrated individual steps of Cu–Cl cycle . Performance of 300‐cm 2 electrolytic cell was evaluated resulting in a stable current density of 0.55 A/cm 2 at 0.7 V, and 98% of the theoretical hydrogen production rate for over 1600 hours was reported .…”
Section: Introductionmentioning
confidence: 99%
“…Canadian national laboratories (CNLs) and the University of Ontario (UOIT) have extensively investigated each step and finally demonstrated individual steps of Cu-Cl cycle. 17,[19][20][21][22] Performance of 300-cm 2 electrolytic cell was evaluated resulting in a stable current density of 0.55 A/cm 2 at 0.7 V, and 98% of the theoretical hydrogen production rate for over 1600 hours was reported. 23 Fivestep Cu-Cl cycle was also studied, and the proof of concept was demonstrated by India at lab scale with H 2 generation rate at 168 mL/h using 1 g of Cu (0.015 mol).…”
mentioning
confidence: 99%
“…Thermochemical water splitting with a copper-chlorine (Cu-Cl) cycle is a promising process involving intermediate copper and chlorine compounds with a net input of water and heat and a net output of hydrogen and oxygen [5,6]. These chemical reactions form a closed internal loop that recycles all chemicals on a continuous basis, without emitting any greenhouse gases.…”
Section: "'%#('#"mentioning
confidence: 99%
“…The numbers of steps (3-steps, 4-steps or 5-steps) have influences on the scale-up challenges and overall cycle efficiencies. A 3-step, 4-step and 5-step cycles of Cu-Cl system for thermochemical water decomposition cycles have been studied extensively [7][8][9] but there is need for comparative studies that can aid in decision making on the most effective and efficient step cycle especially with respect to the second law efficiency of the process [5].…”
Section: "'%#('#"mentioning
confidence: 99%
“…Because the thermal efficiency of Cu‐Cl cycles may be strongly affected by using CuCl/HCl or CuCl electrolyzers, Naterer et al showed that the CuCl/HCl electrolyzer could prevent the copper crossovers and safely produce pure hydrogen gas at low temperature. Wu et al also indicated that the 4‐step Cu‐Cl cycle using CuCl/HCl electrolyzer had a high possibility of commercialization due to the lower grade heat requirement, the less number of equipment, and the higher energy efficiency.…”
Section: Introductionmentioning
confidence: 99%